2019
DOI: 10.1093/rheumatology/kez412
|View full text |Cite
|
Sign up to set email alerts
|

Patients with inflammatory rheumatic diseases: quality of self-reported medical information in a prospective cohort event monitoring system

Abstract: Objectives Assessment of the quality of patient-reported medical information in the Dutch Biologic Monitor and evaluation of the representativeness of the sampled participants. Methods Consecutive adult patients using a biologic DMARD (bDMARD) for an immune-mediated inflammatory disease were included in eight Dutch centres. For this substudy, data of 550 patients with inflammatory rheumatic diseases were used. Patient-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Furthermore, our findings of perfect agreement between self‐report and EHR indicate that patients provide reliable information on their drug use. These results were similar to those of a large rheumatology cohort study that used the same methodology for reporting treatment indication and generic biological use (κ = 0.832 and 96% agreement, respectively) 6 . In addition, all clinically relevant biological changes were reported by patients.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, our findings of perfect agreement between self‐report and EHR indicate that patients provide reliable information on their drug use. These results were similar to those of a large rheumatology cohort study that used the same methodology for reporting treatment indication and generic biological use (κ = 0.832 and 96% agreement, respectively) 6 . In addition, all clinically relevant biological changes were reported by patients.…”
Section: Discussionsupporting
confidence: 83%
“…This prospective multicentre event monitoring study evaluated the quality of patient‐reported information on IBD subtype and IBD drug use during biological treatment, using the Dutch Biologic Monitor 6 . The study was conducted in four medical centers in the Netherlands between January 1, 2017 and December 31, 2018.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dutch Biologic Monitor is a prospective cohort event monitoring model for patient-reported ADRs attributed to biologics [7]. Nine Dutch hospitals participated in the Dutch Biologic Monitor between January 1, 2017 and May 1, 2019.…”
Section: The Dutch Biologic Monitormentioning
confidence: 99%
“…It is a multicentre, web-based cohort event monitoring system that follows patients using biologics mainly for IMIDs. Participating patients complete questionnaires about ADRs they attribute to the biologic treatment, including consequences and experienced burden [7].…”
Section: Introductionmentioning
confidence: 99%